An integrated post-war marketing strategy for tourism development in the de-occupied territories of Ukrainian regions - Tsviliy , Sergiy; Mamotenko, Daria; Bobrykin, Pavlo (Management and Entrepreneurship: Trends of Development, 2026)
The relevance of this article lies in the fact that the implementation of the philosophy and methodology of marketing in the development of tourism in de-occupied territories can ensure their effective functioning under conditions of intense competition and the adverse consequences of war. The purpose of the article is to systematize and substantiate the scientific and methodological foundations and principles for developing an integrated post-war marketing strategy for tourism development in the de-occupied territories of Ukraine, based on the creation and promotion of a territorial tourism brand. The subject of the study is the paradigm of sustainable development of the tourism system, understood as a dynamic process of successive positive post-war transformations. The proposed marketing mechanisms for post-war tourism development in de-occupied regional territories are based on a synthesis of best tourism practices, are comprehensive in nature, and cover all elements of the tourism marketing mix, partnership marketing, and place branding. The integrated approach focuses on both internal and external target audiences and offers a set of specific characteristics and instruments. The measures developed within this framework are aimed at increasing the tourist attractiveness of de-occupied territories, creating conditions for entrepreneurial activity, improving population welfare, restoring tourism infrastructure and resources, and strengthening the competitive position of regions in the interregional division of labor in the tourism sector. The results are recommended for use by central and local authorities of Ukraine, tourism development agencies, stakeholders, and other interested parties in designing and implementing strategies for tourism and regional development in de-occupied territories.JEL Classification: L83, M31, R11, O18, O19